“Orange-Peeling” An innovative fixed tooth preparation technique - RAYYAN, Mohamad; MAAROUF, Rima; ALARJI, Ammar (International Arab Journal of Dentistry (IAJD), 2020)
This report describes an innovative technique of crown preparation, called “Orange-Peeling”, a straight forward technique valuable for increasing accuracy and speed of the procedure. The concept of this new technique evolves about undermining surface enamel by cutting through it from the side rather than grinding throughout the entire hard surface enamel.